Stereoselectivity in the Reduction of Bicyclic Tetramates - Josa-Culleré, Laia; Moloney, Mark G.; Thompson, Amber L. (Synlett, 2016)
The reduction of bicyclic tetramates can be achieved with high levels of diastereocontrol, but small changes in the substitution of the bicyclic lactam system can lead to changes in the steric bias of the concave/convex system. The tetramates and pyroglutamates prepared in this work exhibited limited antibacterial activity.
Keywords: tetramate; reduction; lactam; stereoselectivity; pyroglutamate